Determinant Stock Return in Energy Sector Period 2017 - 2022 - Talahatu, William; Linawati, Nanik (Technology, Business and Entrepreneurship, 2023)
This study aims to analyze the influence of the variables Net Income, Rupiah Exchange Rate, and Operational Cash Flow on stock returns in the energy sector. This research was conducted using time series data for the period 2017-2022. The data analysis method in this research involves the use of a multiple linear regression model to identify the influence of Net Income, Rupiah Exchange Rate and Operational Cash Flow on stock returns in the energy sector during the period 2017-2022. Results This research shows that Net income has a significant effect on stock returns in the energy sector, the Rupiah Exchange Rate has a significant effect on stock returns in the energy sector. Apart from that, Operational Cash Flow does not have a significant effect on stock returns in the energy sector.